KRIYA KULIT KREATIF PENGEMBANGAN WAYANG KULIT PURWA - Ahmadi, Agus (Acintya, 2016)
Creativity is the ability to create something, which always develops in a person, including of crafts works and puppet. The study purposes were reviewed and data analyzed on: the creativity in the craft work, the diversity of puppet craft creations, design the creative puppet development and explain various examples of leather craft works on Purwa puppet development. The study method was adopted qualitative research character. The data analysis was used qualitative reasoning and iconography comparison. From the research results can be formulated the notion of creativity and creative craft creation. In practice of leather craft creation was required of art workmanship foundation, the datasource for exploration, and work practices methods. The diversity of the puppet art in Indonesia it can be noted that there are 55 types of puppets, which are mostly found in Java, and the most popular, widespread, and most of characters forms is the Purwa puppet. In the puppets creation was throughthe process of drawing, pattern or mbabon, inlaid, painting, and finishing. Subsequently reported the form of various creations of leather craft-themed puppet with an explanation, which including of the creation of puppets development for performances, works of leather craft was developed from Purwapuppet element, some new creations puppets, puppet crafts for wall hangings, decorativelighting and puppets patterned shutter, and leather puppets craft for souvenirs.Keywords: puppets, creative, crafts, diversity.